The IMPLEMENTASI NILAI-NILAI MULTIKULTURALISME MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (THE IMPLEMENTATION OF MULTICULTURALISM VALUES THROUGH LEARNING OF ISLAMIC RELIGION EDUCATION): multicultural education and learning of islamic religious education - ALI MIFTAKHU ROSYAD (Risâlah, Jurnal Pendidikan dan Studi Islam, 2019)
Multicultural education is a deliberate attempt to construct human beings who will participate in society as productive citizens. The learning about Islamic religious education has an important role to inculcate multiculturalism values to students which based on holly Quran and hadis in order to be able to create faithful and devoted students to the Almighty God. Besides, the objective of implementation of multiculturalism values in the learning of Islamic religious education is so that students can become civil society that have competence of noble action and be able to actualize it in personal and social life. The success of multicultural education is students marked by differences in culture, race, ethnicity, and religion, so that achieve the equality and a sense of justice, the implementation of multicultural education offers the alternative through the application of strategies and concepts of education based on diversity utilization in the school environment. The multicultural approach is an educational strategy that utilizes the diversity of cultural backgrounds of students as one of the strengths to shape multicultural attitudes. The contribute of this research is to provide thought contributions to teachers and education practitioners about the implementation of multicultural education by utilizing Islamic education education.